FINANCIAL PERFORMANCE ASSESSMENT BASED ON FINANCIAL RATIO ANALYSIS - Elly Lestari; Yuni Setyawati; Paulina Maria Try Kabora (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2023)
Financial performance is the result or achievement that has been achieved by the company's management in carrying out its functions to manage the company's assets effectively during a certain period. This study aims to analyze the factors that affect financial performance at UD Tunas Baru Mulya based on ratio analysis. This type of research used in this research is quantitative with a descriptive approach. Quantitative research methods are one type of research whose specifications are systematic, planned, and measured from the beginning to the design of the research. The data source in this study is secondary data in the form of interviews and financial reports from UD Tunas Baru Mulya. The results of the study note that the liquidity ratio using the current ratio shows that there is an increase in the ratio value of each financial period. The solvency ratio using the debt ratio shows that dependence on debt is very small, and the amount of debt continues to decrease each period. The profitability ratio using profit margin shows that the level of net profit of UD Tunas Baru Mulya continues to increase. The activity ratio shows the value of income earned through sales continues to increase every year. Thus it can be concluded that the financial performance of UD Tunas Baru Mulya is in good condition, therefore UD Tunas Baru Mulya can maintain and increase the level of efficiency in the use of assets in obtaining profits.